A framework for enhancing privacy in online collaboration. (30th May 2022) - Bhardwaj, Aashish; Kumar, Vikas
The COVID-19 pandemic has changed the working of almost all the organisations from physical to online mode, due to its social distancing norms. Working in online mode requires a collaboration platform for sharing documents, audio and video in real time. However, due to poor privacy barriers and ignorance of participants, pranksters, fraudsters and cyber criminals are able to breach the privacy in these collaborations. The present work highlights the privacy features of the popular collaboration tools and their implications for the users. Major privacy breach incidences have been presented along with the associated technological glitches. A privacy enhancement framework has been proposed with six significant pillars as: 1) user centric privacy design; 2) compliance to privacy laws; 3) access control; 4) transparency; 5) awareness and education; 6) ethical contact tracing. The privacy framework will be able to take-up the privacy challenges in online collaboration, if properly implemented. Also, the framework is more user centric rather than organisation centric, hence it can be used by both the individual and institutional users.